2014
DOI: 10.4014/jmb.1402.02054
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization and Molecular Modeling of NAD(P)+-Dependent Succinic Semialdehyde Dehydrogenase from Bacillus subtilis as an Ortholog YneI

Abstract: Succinic semialdehyde dehydrogenase (SSADH) catalyzes the oxidation of succinic semialdehyde (SSA) into succinic acid in the final step of γ-aminobutyric acid degradation. Here, we characterized Bacillus subtilis SSADH (BsSSADH) regarding its cofactor discrimination and substrate inhibition. BsSSADH showed similar values of the catalytic efficiency (kcat/Km) in both NAD(+) and NADP(+) as cofactors, and exhibited complete uncompetitive substrate inhibition at higher SSA concentrations. Further analyses of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Other than the physiological functional study of SSADH in vivo, there were many studies on its catalytical function and cofactor preference in recent years [19][20][21][22]. NADP + or NAD + was required as a hydride acceptor in the reaction of SSA to succinic acid catalyzed by SSADH.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the physiological functional study of SSADH in vivo, there were many studies on its catalytical function and cofactor preference in recent years [19][20][21][22]. NADP + or NAD + was required as a hydride acceptor in the reaction of SSA to succinic acid catalyzed by SSADH.…”
Section: Introductionmentioning
confidence: 99%
“…encoded by gabT and puuE, and also two succinate semialdehyde dehydrogenases (SSADH) encoded by gabD and sad 21,22 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Drosophila melanogaster MalE-DmSSADH showed 7-fold higher activity in the presence of NAD + than NADP + ( Rothacker and Ilg, 2008 ). On the other hand, in the case of YneI, the SSADHs from Bacillus subtilis ( Park et al, 2014 ) and Salmonella typhimurium ( Zheng et al, 2013 ) showed differences in affinity for NAD + or NADP + , but their catalytic efficiency exhibited similar values in both cofactors.…”
Section: Resultsmentioning
confidence: 99%